Workshop on Preparation of Case Method and Team-Based Project Learning Device - Masriani, Masriani; Candramila, Wolly; Lestari, Ira; Sirait, Judyanto; Mirza, Ade; Pasaribu, Revi Lestari; Syamswisna, Syamswisna; Hairida, Hairida; Muharini, Rini; Yeni, Laili Fitri (International Journal of Public Devotion, 2023)
The era of globalization requires students as the nation's next generation to have 21st century skills. However, most students have not received or been trained in 21st century skills while in college. Learning with a constructivist approach with the case method model and team-based project is one strategy to solve this problem, but most of the lecturers in the PMIPA FKIP Untan department have not been able to distinguish and apply the two learning models. This is due to the low understanding of educators related to the case method and team-based project learning models. The aim of this workshop is to improve lecturers' understanding and skills in developing learning tools using the case method and team-based projects. This workshop begins with a presentation of material on the case method and team-based project learning tools using the lecture method and continues with a review of the RPS that has been prepared by the lecturer. All activities are carried out online. The results of the workshop were that 96.5% of the lecturers had understood the RPS using the case method and 93% of the team-based project. As many as 65.5% of lecturers stated that this activity was very helpful in preparing lesson plans with the case method and team-based projects. Meanwhile, 96% of participants wanted to do similar activities again. This indicates that this workshop has provided understanding and assisted participants in preparing lesson plans using the Case Method and Team Based Project. The results of this workshop have motivated lecturers to produce learning tools, especially better lesson plans.